Cognitive impairment across ALS clinical stages in a population-based cohort. (3rd September 2019) - Chiò, Adriano; Moglia, Cristina; Canosa, Antonio; Manera, Umberto; Vasta, Rosario; Brunetti, Maura; Barberis, Marco; Corrado, Lucia; D'Alfonso, Sandra; Bersano, Enrica; Sarnelli, Maria Francesca; Solara, Valentina; et al.
Abstract : Objective: To assess the association of the degree of severity of motor impairment to that of cognitive impairment in a large cohort of patients with amyotrophic lateral sclerosis (ALS). Methods: This is a population-based cross-sectional study on patients with ALS incident in Piemonte, Italy, between 2007 and 2015. Cognitive status was classified according to the revised ALS–FTD Consensus Criteria. The King system and the Milano Torino Staging system (MiToS) were used for defining the severity of motor impairment. Results: Of the 797 patients included in the study, 163 (20.5%) had ALS–frontotemporal dementia (FTD), 38 (4.8%) cognitive and behavioral impairment (ALScbi), 132 (16.6%) cognitive impairment (ALSci), 63 (7.9%) behavioral impairment (ALSbi), 16 (2.0%) nonexecutive impairment, and 385 (48.2%) were cognitively normal. According to King staging, the frequency of cases with ALS-FTD progressively increased from 16.5% in stage 1–44.4% in stage 4; conversely, the frequency of ALSci, ALSbi, and ALScbi increased from King stage 1 to King stage 3 and decreased thereafter. A similar pattern was observed with the MiToS staging. ALS-FTD was more frequent in patients with bulbar involvement at time of cognitive testing. Patients with C9ORF72 expansion (n = 61) showed more severe cognitive impairment with increasing King and MiToS stages. Conclusion: Our findings suggest that ALS motor and cognitive components may worsen in parallel, and that cognitive impairment becomes more pronounced when bulbar function is involved. Our data support the hypothesis that ALS pathology disseminates in a regional ordered sequence, through a cortico-efferent spreading model.